Local Malay snacks and desserts: the hidden gems of Terengganu / Amirul Hakim Zulkifli ... [et al.] - Zulkifli, Amirul Hakim; Mazlan, Nor Hafizah; Talhah, Hasiful Fata; A. W, Mohd Faisal; Wan Ismail, Wan Rusni; Md Nor, Norfezah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
With a unique culture and vibrant tourist attractions, Terengganu has become one of the leading tourism destinations in Malaysia. Apart of stunning sceneries, islands and beaches, Terengganu cuisine has also become a tourism product for both local and foreign tourists. Situated along South China Sea, Terengganu is blessed with abundance of fish, seafood and coconut tree which become the main ingredients for most of its cuisines. Resulting from the acculturation of its neighbouring cultures, the cuisine is the melting pot of flavour from Malay and Thai. Nasi Dagang, Nasi Kerabu, Keropok Lekor, Sata, Bekang, Bronok, Qasidah, and Asam Gumpal are the iconic foods that are widely highlighted by the tourism authority. Besides all the prominent local cuisines in Terengganu there are still local cuisines that are hidden from the eyes of the public. Therefore, this paper focuses to explore Terengganu traditional Malay foods that are not typically promoted as tourism product. The study is based on secondary data gathered from journals, articles and tourism manuals. It is found that, there are aplenty other unnoticed foods that are unique to the state. These signature foods are vastly potential as attractive tourism products. This conceptual paper provides scholars and practitioner a great potential of insight view towards food as a unique identity of Terengganu that can be utilized as tourism product. Subsequently, it will lead to a well-planned strategy in order to upsurge the locals’ income and boosting the state’s economy.